A Plasmid-Transposon Hybrid Mutagenesis System Effective in a Broad Range of Enterobacteria - Monson, Rita; Smith, Debra S.; Matilla, Miguel A.; Roberts, Kevin; Richardson, Elizabeth; Drew, Alison; Williamson, Neil; Ramsay, Josh; Welch, Martin; Salmond, George P. C. (Frontiers in Microbiology, 2015)
Random transposon mutagenesis is a powerful technique used to generate libraries of genetic insertions in many different bacterial strains. Here we develop a system facilitating random transposon mutagenesis in a range of different Gram-negative bacterial strains, including Pectobacterium atrosepticum, Citrobacter rodentium, Serratia sp. ATCC39006, Serratia plymuthica, Dickeya dadantii and many more. Transposon mutagenesis was optimized in each of these strains and three studies are presented to show the efficacy of this system. Firstly, the important agricultural pathogen D. dadantii was mutagenized. Two mutants that showed reduced protease production and one mutant producing the previously cryptic pigment, indigoidine, were identified and characterized. Secondly, the enterobacterium, Serratia sp. ATCC39006 was mutagenized and mutants incapable of producing gas vesicles, proteinaceous intracellular organelles, were identified. One of these contained a β-galactosidase transcriptional fusion within the gene gvpA1, essential for gas vesicle production. Finally, the system was used to mutate the biosynthetic gene clusters of the antifungal, anti-oomycete and anticancer polyketide, oocydin A, in the plant-associated enterobacterium, Dickeya solani MK10. The mutagenesis system was developed to allow easy identification of transposon insertion sites by sequencing, after facile generation of a replicon encompassing the transposon and adjacent DNA, post-excision. Furthermore, the system can also create transcriptional fusions with either β-galactosidase or β-glucuronidase as reporters, and exploits a variety of drug resistance markers so that multiple selectable fusions can be generated in a single strain. This system of various transposons has wide utility and can be combined in many different ways.